Phosphorylation at Ser 727 Increases STAT3 Interaction with PKCε Regulating Neuron–Glia Crosstalk via IL-6-Mediated Hyperalgesia In Vivo and In Vitro - Li, Xiongjuan; Zhou, Biqiang; Yang, Han; Yang, Xinping; Zhao, Zhao; Pan, Zhenglong; Liao, Xinran; Jian, Wenling; Liu, Yuqiang; Lu, Han; Xue, Qingsheng; Luo, Yan; et al. (Mediators of Inflammation, 2022)
Background and Aim. Interleukin-6 (IL-6) modulates neurons–glia crosstalk and subsequently triggers hyperalgesia. This study is aimed at investigating whether the interaction between protein kinase C epsilon (PKCε) and signal transducer and activator of transcription 3 (STAT3) mediated IL-6-induced hyperalgesia and neurocyte activation. Methods. A rat hyperalgesia model was induced using an intraplantar injection of Freund’s complete adjuvant (FCA) or an intrathecal injection of IL-6. Mechanical allodynia was evaluated using von Frey filament tests after intrathecal injections of T-5224 (c-Fos/AP-1 inhibitor), minocycline (Mino, a specific microglia inhibitor), L-2-aminoadipic acid (LAA, an astroglial toxin), PKCε inhibitor peptide, APTSTAT3-9R (STAT3 inhibitor), or anti-IL-6 antibody. The c-Fos, GFAP, Iba-1, PKCε, STAT3, pSTAT3Tyr705 and pSTAT3Ser727, and IL-6 expression at the spinal cord level was assessed by Western blot analysis. The interactive effects of PKCε and STAT3 were determined using immunofluorescence staining and immunoprecipitation in vivo and in vitro. Interleukin-6 promoter activity was examined using luciferase assays. Results. T-5224, Mino, and LAA attenuated FCA- or IL-6-mediated inflammatory pain, with a decrease in c-Fos, GFAP, Iba-1, PKCε, and IL-6 expression. PKCε inhibitor peptide and APTSTAT3-9R reversed FCA-induced nociceptive behavior, while decreasing pSTAT3Ser727, IL-6, c-Fos, GFAP, and Iba-1 expression and PKCε and STAT3 coexpression. Interleukin-6 promoter activity increased in the presence of PKCε and STAT3. The interaction with PKCε increased on phosphorylating STAT3 at Ser727 but not at Tyr705. Conclusion. STAT3 phosphorylation at Ser 727 and the interaction with PKCε contribute to hyperalgesia via the IL-6-mediated signaling pathway, thus regulating neuron–glia crosstalk during inflammatory pain.